Traditional masonry and archaeological restoration. A case study from Salūt, Oman - Stefano Bizzarri; Michele Degli Esposti; Caterina Careccia; Tiziana de Gennaro; Elisa Tangheroni (Loggia, Arquitectura & Restauración, 2021)
This paper shows the restoration work carried out on the mudbrick structures uncovered at the Iron Age (c. 1300-300 BC) site of Salūt, in central Oman. In the region, traditional earthen architecture represented the key building technique until modern times. The traditional concept of constant upkeep is arguably the only way of efficiently preserving ancient structures. However, different mud plaster compositions were tested which could provide a better aspect and a lower static load on the structures. The work strategy was meant to be sustainable from an economic, ecological, and sociological point of view, as it also aimed at documenting and hopefully reviving the traditional earthen architecture currently endangered by the disinterest of younger generations.